Detection of EGFR mutation of pulmonary adenocarcinoma in sputum using droplet digital PCR - Isaka, Tetsuya (BMC Pulm Med, 2021)
BACKGROUND: It is still unclear whether epidermal growth factor receptor (EGFR) mutation of primary lung adenocarcinoma can be detected on sputum samples. This study aimed to examine EGFR mutations of primary lung adenocarcinoma in sputum samples using droplet digital polymerase chain reaction (ddPCR) and compare it with an EGFR mutation in surgically resected lung cancer. METHODS: Sputum was prospectively collected from the patients before complete resection of the primary lung cancer at Kanagawa Cancer Center from September 2014 to May 2016. ddPCR was performed to detect EGFR exon 21 L858R point mutation (Ex21) and EGFR exon 19 deletion mutation (Ex19) in sputum samples from patients with lung adenocarcinoma. The concordance of EGFR mutation status in sputum samples and tumors in surgically resected specimen was evaluated for each positive and negative cytology group. RESULTS: One hundred and eighteen patients with primary lung adenocarcinoma provided sputum samples. Sputum cytology was positive in 13 patients (11.0%). ddPCR detected two cases of Ex21 and two cases of Ex19 in sputum cytology positive cases. Compared to surgically resected specimens, the sensitivity, specificity, and positive predictive value of EGFR mutation (Ex19 and Ex21) detection were 80.0%, 100%, and 100%, respectively, in sputum cytology positive cases. In contrast, the sensitivity, specificity, and positive predictive value of EGFR mutation (Ex19 and Ex21) detection were 3.1%, 100%, and 100%, respectively, in sputum cytology negative cases. CONCLUSIONS: EGFR mutations in primary lung adenocarcinoma can be detected with high sensitivity in sputum samples if sputum cytology is positive.